Prognostic Significance of Immunohistochemical Phenotypes in Patients Treated for High-Grade Cervical Intraepithelial Neoplasia. (18th December 2013) - Origoni, Massimo; Parma, Marta; Dell'Antonio, Giacomo; Gelardi, Chiara; Stefani, Chiara; Salvatore, Stefano; Candiani, Massimo
Abstract : Strong evidence exists that the host's immune system plays a crucial role for the development of human papillomavirus-related cervical premalignant and malignant lesions. In particular, effective cell-mediated immunity (CMI) promotes spontaneous infection clearance and cancer precursors regression in healthy subjects, while immunosuppressed individuals are more likely to experience infection persistence, cervical intraepithelial neoplasia (CIN) lesions, and cervical cancer. In this study, the prognostic significance of immunohistochemical profiling of CD4+ T-cells, CD8+ T-cells, dendritic cells (CD11c+), T-bet+, and GATA-3+ transcription factors has been studied in surgical specimens of 34 consecutive women affected by high-grade cervical intraepithelial neoplasia (CIN2-3) submitted to cervical conization. Results have been correlated with the clinical outcomes at 24 months after treatment and statistically analyzed. Higher rates of CD4+ T-cells, CD11c+ dendritic cells, and T-bet+ transcription factor positivity showed a strong statistically significative correlation with favourable clinical outcomes (P ≤ 0.0001 ). These data reinforce the evidence of the relevance of the host's immune status in the natural history of HPV-related cervical disease and add a prognostic significance of the cervical immunological profile in terms of predicting significant lower recurrence rates.